الحماية الجنائية للمرأة في الفضاء الرقمي وفق مستجدات القانون 103.13 - شرف، ياسين (محمد أمين اسماعيلي, 2023)
يثير هذا المقال، الحماية الجنائية المقررة لفائدة المرأة من الجرائم الماسة بحياتها الخاصة، والمرتكبة داخل البيئة الرقمية، سواء من ما تعلق بالجانب الموضوعي (التجريم والعقاب(، أو فيما يهم الرعاية اللاحقة للنساء ضحايا العنف -العنف الرقمي على وجه الخصوص-، فإذا كان المشرع المغربي قد أحسن صنعا لما أخرج إلى الوجود القانون 103.13 المتعلق بمحاربة العنف ضد النساء -أخص بالذكر العنف الرقمي- فإن تطور الجريمة السبرانية وتنوع طرق ووسائل ارتكابها من جهة، وغموض المفاهيم الجنائية وعدم دقتها من جهة ثانية، جعل تطبيق القواعد الجنائية على هذه الجرائم من طرف رجال القضاء يتسم بالصعوبة والتي تتجلى في خرق المبادئ العامة المنظمة للقانون الجنائي كمبدأ الشرعية الجنائية، بسبب اللجوء إلى القياس بين فعل مجرم وأخر مستجد غير مجرم في اختلاف تام للعناصر المكونة لكل منهما، أضف لذلك غياب الحماية المقررة للمرأة ضحية العنف الرقمي خلال مرحلة الشكاية والتحقيق على الخصوص، وكذا ضعف عمل الخلايا المحدثة على مستوى المحاكم الذي مرده لغياب التخصص والتكوين. This article, raises the criminal protection for women against crimes against their private lives committed within the digital environment, both on the substantive side. (Criminalization and punishment), or in the aftercare of women victims of violence - Digital violence in particular. If the Moroccan legislature had done well, it would not have come into existence law 103.13 on combating violence against women. In particular, digital violence - the evolution of cybercrime and the diversity of ways and means of committing it on the one hand and the vagueness and inaccuracy of criminal concepts, on the other hand, make the application of criminal rules to such crimes by the judiciary difficult and manifest itself in the violation of the universal principles governing criminal law as the principle of criminal legality ", because of the use of analogy between the act of a criminal and the last new offender, which is not criminally different from each other's constituent elements, Add to this the lack of protection for women victims of digital violence during the complaint and investigation phase in particular as well as the weak functioning of upgraded cells at the court level due to the lack of specialization and composition.
Keywords: الجرائم الرقمية -- ظاهرة العنف -- العنف ضد المرأة -- الحماية الجنائية -- قانون العقوبات